Research utilization among nurses: barriers and facilitators - Sapkato, S (Journal of Chitwan Medical College, 2015)
Research utilization is the implementation of research-based findings in practice clinical setting to provide services to consumers. It is the critical way to strengthen the discipline and practice of nursing to provide quality nursing care to consumers of nursing that may be individual, family or community but different factors/barriers preventing the nurses to implement the research finding into the practice. The aims of this article are firstly to introduce about research utilization among nurses, secondly to present barriers of research utilization to nurses and lastly to discuss the ways of promoting research utilization among nurses in developed and developing countries like Nepal. For these purposes, different electronic and database literatures related to research utilization among nurses are searched, reviewed and presented here to by giving meaningful organization and presentation. This article presents progress in development of research utilization in developed and developing countries, barriers of research utilization including valid scale to measure barriers of research utilization and ways of promoting research utilization among nurses. Most common barriers that prevent nurses from implementing research findings include not having enough time; lack of institutional or financial support; insufficient support from colleagues; shortage of personnel and resources; not able to understand research reports; lack of knowledge; and the dependence of nurses on doctors and managers in making changes in clinical practice. DOI: http://dx.doi.org/10.3126/jcmc.v4i4.11955